3(x+4)+2x=5(x+2)

Simple and best practice solution for 3(x+4)+2x=5(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+4)+2x=5(x+2) equation:


Simplifying
3(x + 4) + 2x = 5(x + 2)

Reorder the terms:
3(4 + x) + 2x = 5(x + 2)
(4 * 3 + x * 3) + 2x = 5(x + 2)
(12 + 3x) + 2x = 5(x + 2)

Combine like terms: 3x + 2x = 5x
12 + 5x = 5(x + 2)

Reorder the terms:
12 + 5x = 5(2 + x)
12 + 5x = (2 * 5 + x * 5)
12 + 5x = (10 + 5x)

Add '-5x' to each side of the equation.
12 + 5x + -5x = 10 + 5x + -5x

Combine like terms: 5x + -5x = 0
12 + 0 = 10 + 5x + -5x
12 = 10 + 5x + -5x

Combine like terms: 5x + -5x = 0
12 = 10 + 0
12 = 10

Solving
12 = 10

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| n-8=-21 | | -5n(5n-6)=0 | | 3r^2+3r-6=0 | | -2y=-4y+24 | | 6m^2-72+216=0 | | 2v^2-14v+12=0 | | 3x+2+6x+11+5x-1=180 | | 3y-2y(y+19)=9y-3(9-y) | | -6(4d+5)+7d=-2d | | 33y-6y=-18-36 | | -(p+17)=4p-2 | | 3x-15+2=-20 | | 10-16=12x-6x-3x-3 | | p+0.77=9.3 | | 0.3+0.6(25-c)=12 | | 5x-1=6x+11 | | 2.7h+15=0.3(10-h) | | y=4x^2-x^2 | | 200=3x+2 | | 5x-4-7x=3x+6 | | 200=3x+7 | | 9(8d*5)+13=12d-2 | | -15=-6+x | | 4r-10=2r+16 | | 5(4-2y)=8(3y-2) | | -3(6a-3)+8a=-1 | | 3.1t+7=2.6 | | 3x-6=8x-26 | | 0.8(y-5)=10 | | 5(3k-2)=4(3-5k) | | -9(2-y)-(2-y)=2 | | -x-4=3x-4 |

Equations solver categories